Symbolism in Katherine Anne Porter's Short Story Rope (NOBEL: Journal of Literature and Language Teaching, 2018)
Abstract This study aims to examine the use of a symbol and narration technique in Katherine Anne Porter’s short story Rope. The story is about a married couple who gets into an argument due to a bundle of rope. This study examines how the author describes the psychological state of the couple through their reaction over the rope. The data sources are the short story Rope and related articles. The data was collected by close reading. The collected data are analyzed by applying symbolism theory and examining the narration technique. The findings show that the argument over the rope reveals the wife’s hidden frustrations and her husband’s inability to understand her troubles. Keywords: Symbol; rope; frustration; Katherine Anne Porter; narration